Unilateral pulmonary edema after minimally-invasive redo-double valve replacement procedure—case report - Wang, Dan; Yang, Jia; Ren, Haibo (Frontiers in Cardiovascular Medicine, 2025)
This case report describes a patient with a history of mechanical aortic and mitral valve replacements who developed prosthetic valve stenosis years later and underwent a minimally invasive, thoracoscopic-assisted double valve re-replacement. Postoperatively, the patient developed a rare but life-threatening re-expansion pulmonary edema (RPE), which led to severe acute respiratory distress syndrome (ARDS), with rapid deterioration into refractory hypoxemia. Despite comprehensive conventional supportive management—including lung-protective ventilation, diuresis, anti-inflammatory therapy, and other measures—adequate oxygenation could not be maintained. Venovenous extracorporeal membrane oxygenation (VV-ECMO) was emergently initiated. With ECMO support, the patient's lungs were able to rest and recover. After 10 days of support, ECMO was successfully discontinued, and the patient eventually recovered and was discharged. This case aims to explore the pathophysiological mechanisms of RPE, management strategies for complications following minimally invasive cardiac surgery, and to emphasize the critical role of VV-ECMO in treating refractory respiratory failure, as well as the importance of multidisciplinary team (MDT) collaboration.